Outcome of Wide Local Excision in Idiopathic Granulomatous Mastitis-A Short Observational Study - Alam, Afroza E; Shaheed, Nusrat; Khatun, Mahabuba; Zaman, Mohammed Rashed Uz; Akter, Nazneen; Hosen, Md Abul (Central Medical College Journal, 2024)
Background: Idiopathic granulomatous mastitis is a rare disease of the breast. It is a benign inflammatory lesion characterized by lobulocentric granulomas. Clinically and radiologically it may mimic breast carcinoma.1 Awareness of surgeons, pathologists, and radiologists is essential to avoid unnecessary mastectomies. Objective: This study aimed to investigate the outcome of wide local excision in idiopathic granulomatous mastitis. Method: This hospital based prospective study was done in surgery unit of both govt. and private hospitals, Cumilla, Bangladesh. All patients who were diagnosed with idiopathic granulomatous mastitis during the period of July 2020 to July 2022 were included. Informed consent was taken from the patient before invasive procedures including surgery. Data was analyzed using the Statistical Package for Social Sciences version 24.0 wherever appropriate. Result: Among 17 patients no recurrence was observed in 94% patients who were treated with wide surgical excision during the median follow-up period of 12 months. Conclusion: Patients with idiopathic granulomatous mastitis can present with a wide variety of symptoms which mimic other more common conditions. Surgical management in the form of wide local excision appears to provide the best long term outcome in patients with idiopathic granulomatous mastitis. Central Medical College Journal Vol 8 No 1 January 2024 Page: 35-37